PENDIDIKAN SEJARAH LOKAL DALAM KONTEKS MULTIKULTURALISME - Supardi Supardi (LPMPP Universitas Negeri Yogyakarta, 2006)
AbstractMulticulturalism is a concept which admit cultural differentiations in the egality and equality. This concept is still relevance in the nation concept that has cultural differentiations such as Indonesian. Education is one of an effective media for multiculturalism development. Historicaleducation, as a concept, is aimed to build a democracy, nationalism, and multiculturalism character.One of the historical unit which has studied heterogeneous of Indonesia is local history. This article supposes to identify; 1) how the role of local history education builds multiculturalism, 2) how the concept of effectivity of local history education develop multiculturalismcharacter.The local history studies can give the historical awareness of society differentiations for students. The studies of socials differentiation in last time, will shape multiculturalism characters. Local history teaching can be done with three models; 1) out class history teaching, 2) team teaching among social studies teachers, and 3) insert local history in the subjects that is relevance with National History.Key words: multiculturalism, local history, education